Media Exposure, Perceived Efficacy, and Protective Behaviors in a Public Health Emergency. - XIGEN LI (International Journal of Communication (19328036), 2018)
Based on the extended parallel process model and social cognitive theory, this study developed and tested a model of media exposure, perceived efficacy, and protective behaviors in a public health emergency. The findings from a survey of 717 Hong Kong residents show that media exposure had variant effects on perceived societal-level risks and personal-level risks. The study introduced the three aspects of perceived efficacy as the predictors of health protective behaviors. It found that self-efficacy, collective efficacy, and proxy efficacy varied in their effects on danger control and fear control outcomes. Self-efficacy and proxy efficacy positively predicted danger control outcomes, whereas proxy efficacy negatively predicted fear control outcomes. The effect of perceived threat on danger control outcomes was present as self-efficacy increased.